European Integration Content of the Danube - A Factor of Intercultural Education of Student Youth : Array - Kichuk, Nadezhda; Kurilyak, Yuriy (Journal of Danubian Studies and Research, 2021)
The European integration content provided by the Danube River contributes to the successful solution of the problem of intercultural education of the younger generation. The origins, in particular of the Danube Bessarabia, go back centuries, from the Tripoli culture. This circumstance in cultural studies largely explains the factor of polyethnicity of the society of the Ukrainian Danube region, which determines the centuries-old interpenetration of cultures of representatives of different ethnic groups, the need to take into account the upbringing of the younger generation on the priorities of universal values ​​and the imperative of European integration. Some interactive forms of work with students have been detailed, where the celebration of the International Danube Day is the basic one.